Light spectrum effects on micropropagation and gene expression of Bucephalandra sp. in a temporary immersion system for sustainable production - Laksana, Chanakan; Sophiphun, Onsulang; Kaewhom, Paitoon; Chanprame, Sontichai (Frontiers in Plant Science, 2025)
Bucephalandra sp. ‘Wavy Dark Green’ is a commercially valuable ornamental aquatic plant with limited propagation potential due to low multiplication rates and acclimatization challenges. This study aimed to developed an integrated tissue culture protocol by optimizing disinfection procedures, basal media and plant growth regulator, temporary immersion system (TIS) conditions, light quality, and rooting and acclimatization methods. Surface sterilization using 0.1–0.2% HgCl2 or a two-step 1.2% NaOCl protocol significantly improved explant survival and reduced contamination. MS medium supplemented with 5 mg/L benzylaminopurine (BA) produced the highest shoot proliferation on solid culture media. In TIS, six immersions per day for 2–3 minutes yielded optimal shoot multiplication and biomass. Blue:red (70:30) and pure blue light enhanced chlorophyll content, photosynthetic efficiency (QY), stomatal opening, and upregulated key light-responsive genes (psaA, psbB, petG, pskB, atpA, petA). Rooting was most effective in ¼ or full-strength MS medium with 0.3 mg/L naphthaleneacetic acid (NAA). Acclimatized plantlets grown in sand exhibited the highest survival and growth. This integrated protocol supports efficient micropropagation and ex vitro establishment of Bucephalandra sp. ‘Wavy Dark Green’, facilitating its conservation, ornamental use, and sustainable export, in line with SDG 12 (Responsible Consumption and Production).